MARKETING ESTRATÉGICO Y COSTOS EN LA GLOBALIZACIÓN DE LOS MERCADOS. - Mayuri Barrón, Jorge V. (2009)
In the global marketplace that live micro-enterprise, small, medium or large, whatever its size, it has to be competitive. To achieve this objective, marketers go to tools such as Auditing and Costs. This is how appears a new discipline: Strategic Marketing, based on the principle stated by Peter Drucker: “Make what you can sell, rather than trying to sell what you can make”. This article aims to demonstrate the importance of integrating Auditing and Costs disciplines which are communicating vessels working together to be of service to the company to achieve its objectives, making a warning call to managers, accountants and economists to be interested on these current issues.